Two Case Reports of Neuropsychological Functioning in Congenital Insensitivity to Pain with Anhidrosis (CIPA) (2020)
Individuals with congenital insensitivity to pain with anhidrosis (CIPA) are reported to have intellectual disability but to our knowledge, no detailed study about neuropsychological functioning of this condition has ever been published. The present study assessed neuropsychological outcomes of two children with CIPA using standardized neuropsychological tests. The neuropsychological assessment revealed difficulties in a wide range of cognitive, executive, and integrative functions, such as a behavioral and adaptive level. Both children with CIPA functioned in the intellectual disability range with symptoms related to an executive dysfunction and negative-oriented personal emotional processing, and limitations in academic and self-care skills.